2006
DOI: 10.1529/biophysj.105.075788
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Aged in Plasma Forms Clusters Resembling Subendothelial Droplets: Aggregation via Surface Sites

Abstract: In early phases of atherogenesis, droplets and vesicles accumulate in the subendothelial extracellular space of arterial intima. There is much evidence to suggest that these droplets, ranging between 100 and 400 nm, derive from modified low-density lipoprotein (LDL). In investigations of the formation mechanism of these droplets, LDL fusion was previously induced in vitro by proteolysis, lipolysis, oxidation, and vigorous shaking, but all treatments failed to reproduce the size distribution range of in vivo dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
6
30
0
Order By: Relevance
“…It has been reported that active Lys are clustered in basic microenvironments, some of them being involved in LDLr recognition (11)(12)(13). These conformational differences between LDL(+) and LDL(-) agree with the observation of misfolded apoB-100 in LDL(-) ( 9 ), a property that increases its overall amyloidogenic propensity ( 10 ) and could also be involved in its higher susceptibility to particle aggregation ( 7,8 ).…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported that active Lys are clustered in basic microenvironments, some of them being involved in LDLr recognition (11)(12)(13). These conformational differences between LDL(+) and LDL(-) agree with the observation of misfolded apoB-100 in LDL(-) ( 9 ), a property that increases its overall amyloidogenic propensity ( 10 ) and could also be involved in its higher susceptibility to particle aggregation ( 7,8 ).…”
Section: Discussionsupporting
confidence: 58%
“…The latter may involve apoB residues 405-539 (MB24 binding site) or 1022-1031 (MB11 binding site) ( Fig. 5 ), which are located in relative proximity on LDL surface ( 31 ). We speculate that targeting conformational changes in apoB that prime LDL for fusion may provide a strategy for blocking this pathogenic reaction before it occurs.…”
Section: Effect Of the Particle Size On Ldl Fusion: Potential Metabolmentioning
confidence: 99%
“…Although the detailed structural basis for LDL fusion is unclear, it is thought to result from accumulation of packing defects on LDL surface that form upon mechanical, thermal, chemical or enzymatic perturbations (9)(10)(11)(12)(13)(14)(15)(29)(30)(31)(32). The latter include lipolysis of polar lipids, such as phosphatidylcholine or sphingomyelin, and proteolysis of apoB followed by dissociation of its proteolytic fragments (7)(8)(9)(10)(11)(12)(13)(14)(15)32 ).…”
Section: Circular Dichroism and Turbidity Measurementsmentioning
confidence: 99%
“…For example, minimal lipolytic activity of secretary PLA 2 was observed when freshly isolated plasma LDLs were used as substrates; however, lipolytic activity increased up to 25-fold upon LDL storage at 6°C for 8 weeks or at 37°C for 15 h, which was probably due to PC oxidation (81). In another study, plasma incubation at 37°C produced a subpopulation of LDLs that were prone to aggregation, fusion, and lipid droplet formation as detected by dynamic light scattering and atomic force microscopy (82). Kinetics analysis suggested that particle aggregation in these experiments was driven by interactions between a limited number of specific surface sites on LDLs (82).…”
Section: Biochemical Modificationsmentioning
confidence: 99%